Evaluasi Program Magang Generasi Bertalenta (MAGENTA) dalam Menarik dan Mempertahankan Kandidat Berkualitas - Hana Nurkhairani; Christian Wiradendi Wolor; Wida Aristanti (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2026)
The Generasi Bertalenta Internship Program (MAGENTA) represents a strategic initiative of Perum BULOG aimed at developing and attracting competent human resources. This study seeks to evaluate the implementation of the MAGENTA Program in terms of its effectiveness in attracting and retaining qualified candidates within the organization. A qualitative research approach with a case study design was employed. Data were obtained through in-depth interviews, direct observations, and document analysis involving internship participants and program administrators at Perum BULOG. The data were analyzed using the stages of data reduction, data presentation, and conclusion formulation. The findings reveal that the MAGENTA Program requires further evaluation, particularly regarding the alignment between participants’ competencies and the organizational needs. Moreover, a key challenge identified is the limited opportunity for internship participants to be involved in the company’s strategic projects, which restricts the optimal utilization of their potential. The study concludes that although the MAGENTA Program contributes to attracting qualified candidates, its effectiveness in retaining such candidates remains limited. Therefore, improvements in competency mapping, placement planning, and the assignment of more strategic roles are essential to enhance the overall effectiveness of the program.